2022
DOI: 10.3389/fnut.2022.871682
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intermittent Fasting in Human Compared to a Non-intervention Diet and Caloric Restriction: A Meta-Analysis of Randomized Controlled Trials

Abstract: BackgroundThe popularity of applying intermittent fasting (IF) has increased as more and more people are trying to avoid or alleviate obesity and metabolic disease. This study aimed to systematically explore the effects of various IF in humans.MethodsThe randomized controlled trials (RCTs) related to IF vs. non-intervention diet or caloric restriction (CR) were retrieved in PubMed, Web of Science, Cochrane Library database, and Embase. Extraction outcomes included, but were not limited to, weight, body mass in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 80 publications
5
47
1
Order By: Relevance
“…When compared with an ad libitum diet, 10 reviews found fasting glucose to be significantly reduced during IF, 10,16,21,22,24,29,30,[40][41][42] whereas nine reviews found that there was no significant difference compared to an ad libitum diet. 5,6,13,17,20,25,26,28,37 All seven reviews that reported HbA1c levels found no significant difference between IF and control groups. 5,14,21,25,29,30,37 Four of these reviews did not include any participants with T2D and therefore most participants did not have any glucose abnormalities at baseline.…”
Section: If Versus Ad Libitummentioning
confidence: 98%
See 2 more Smart Citations
“…When compared with an ad libitum diet, 10 reviews found fasting glucose to be significantly reduced during IF, 10,16,21,22,24,29,30,[40][41][42] whereas nine reviews found that there was no significant difference compared to an ad libitum diet. 5,6,13,17,20,25,26,28,37 All seven reviews that reported HbA1c levels found no significant difference between IF and control groups. 5,14,21,25,29,30,37 Four of these reviews did not include any participants with T2D and therefore most participants did not have any glucose abnormalities at baseline.…”
Section: If Versus Ad Libitummentioning
confidence: 98%
“…6,11,12,[15][16][17]20,21,[23][24][25]27,29,30 IF versus CER Nineteen reviews found a comparable weight loss following IF and CER. [4][5][6]11,18,19,23,[25][26][27][31][32][33][34][35][36][37][38][39] In terms of BMI change, five reviews compared IF to CER, finding no significant difference between the two interventions. 11,25,27,38,39…”
Section: If Versus Ad Libitummentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Ramadan fasting reduced the gene expression of "fat-mass-andobesity-associated protein" (FTO) in overweight/obese individuals 153 , which has been associated with obesity 154 despite lower calorie intake 155 . However, it is currently a matter of debate whether IF (i.e., time-dependent calorie restriction) is more effective 156 or equally effective 157,158 than continuous calorie restriction (e.g., hypocaloric diet), and whether it is effective if no calorie restriction/dietary counselling is applied 159 . In the setting of type-2 diabetes mellitus 160 , close monitoring of diabetes medication and blood glucose is needed due to concerns about hypoglycemia 161 although TRF has also been shown to be effective and safe in overweight/obese patients with type-2 diabetes mellitus.…”
Section: Intermittent Fastingmentioning
confidence: 99%
“…IF is fundamentally a timing strategy that manipulates the placement and nature of feeding and fasting intervals, which can be stratified into two main categories: (1) intra-weekly fasting (alternate-day fasting/ADF, twice-weekly fasting/TWF) and (2) intra-daily fasting (early time-restricted eating/eTRE and delayed time-restricted eating/dTRE). A growing body of evidence indicates that IF is a viable alternative to daily caloric restriction (DCR), showing similar effectiveness for weight loss [ 3 , 4 ] and alleviating cardiometabolic risk factors [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%